2021
DOI: 10.3390/v13081427
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment in Children Exposed to Zika Virus: What Are the Consequences for Children Who Do Not Present with Microcephaly at Birth?

Abstract: The relation of Zika virus (ZIKV) with microcephaly is well established. However, knowledge is lacking on later developmental outcomes in children with evidence of maternal ZIKV infection during pregnancy born without microcephaly. The objective of this analysis is to investigate the impact of prenatal exposure to ZIKV on neuropsychomotor development in children without microcephaly. We evaluated 274 children including 235 ZIKV exposed and 39 controls using the Bayley-III Scales of Infant and Toddler Developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…A study in the West Indies reported that children exposed to ZIKV during pregnancy without CZS had similar rates of abnormal neurodevelopment between 22 and 30 months of age compared with ZIKV-unexposed peers [78 ▪ ]. In a longitudinal Brazilian study of 235 normocephalic children exposed to ZIKV during pregnancy assessed using the Bayley-III between 6 and 42 months, 9.4, 12.3, and 4.7% showed mild–moderate delays in the cognitive, language, and motor scores, respectively; however, they did not find increased developmental concerns compared with 39 unexposed children [79 ▪ ]. Differences in duration of follow-up, number of cases and controls, neurodevelopmental outcome measures, and social–economic or environmental factors may be reasons for different findings.…”
Section: Neurological and Developmental Outcomes Of Congenital Infect...mentioning
confidence: 87%
“…A study in the West Indies reported that children exposed to ZIKV during pregnancy without CZS had similar rates of abnormal neurodevelopment between 22 and 30 months of age compared with ZIKV-unexposed peers [78 ▪ ]. In a longitudinal Brazilian study of 235 normocephalic children exposed to ZIKV during pregnancy assessed using the Bayley-III between 6 and 42 months, 9.4, 12.3, and 4.7% showed mild–moderate delays in the cognitive, language, and motor scores, respectively; however, they did not find increased developmental concerns compared with 39 unexposed children [79 ▪ ]. Differences in duration of follow-up, number of cases and controls, neurodevelopmental outcome measures, and social–economic or environmental factors may be reasons for different findings.…”
Section: Neurological and Developmental Outcomes Of Congenital Infect...mentioning
confidence: 87%
“…In addition to their role in causing swallowing disorders, ZIKV-related neurological impairments may also lead to challenges with introducing solid foods and with acquiring motor skills for performing the eating-related tasks required to attain an appropriate diet. Some recent studies have suggested that the greater the severity of ZIKV-related microcephaly, the greater the impairment of neurodevelopment in children [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, not all children with prenatal ZIKV exposure are at risk. Although ZIKV targets neural stem cells in the developing brain, neurological manifestations are not apparent at birth in the majority of ZIKV-exposed children [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%